Agricultural value of Black Soldier Fly larvae frass as organic fertilizer on ryegrass. Issue 1 (January 2021) - Menino, Regina; Felizes, Fernando; Castelo-Branco, Maria Amélia; Fareleira, Paula; Moreira, Olga; Nunes, Rui; Murta, Daniel
Abstract: Hermetia illucens L., known as Black Soldier Fly (BSF) appear as an opportunity to reuse vegetable by-products, as it is easy to reproduce and can be reared in agricultural side streams, allowing the production of both, animal feed (the larvae, after recycling of the vegetal debris) and soil organic fertilizer (insect frass). Although several organic fertilizers, from long ago, have been used in agriculture, there is yet a paucity of experimental data on the evaluation of the fertilization potential of BSF larvae frass (BSFF). The present study is a contribution to access the agronomic and environmental potential of the BSFF as an organic fertilizer. Within this aim, it was conducted a greenhouse experiment with ryegrass, using seven treatments of BSFF. Under the experimental conditions, the results showed a significant effect of BSFF on the overall ryegrass production, with a steady increase (significant at p ≤ 0.05, as accessed through the Tukey test) up to the treatment with a greater rate of application. In what concerns sustainability of soil productivity, at the end of the experiment, there was also positive indications, namely, a significant increase of OM, P and K, for treatments with higher N endowments, together with a constant increase of dehydrogenase activity, from the control to the higher treatment, which was significant for treatments receiving the higher dose of BSFF. Abstract : Black soldier fly larvae, Organic fertilizer, Pot trial, Perennial ryegrass, Entomocompost.